ANALYSIS POLICE EFFORTS IN CLEAR HER NAME DUE TO FALSE ARREST ACCORDING TO ARTICLE 1, ITEM 23 ABOUT REHABILITATION ARREST CRIMINAL CODE - Dadang Suprijatna (JURNAL HUKUM DE'RECHTSSTAAT, 2015)
ABSTRACTPositions wrongly in Indonesia's criminal justice system was relatively less attention, and yet provide direct protection against the victim. Criminal law policy for the protection of victims of wrongful arrest of a criminal offense, used with an integral approach and balance between penal policies (penal policy) and non penal policy (non penal policy) in order to achieve the welfare of the community.  The method used in this research is a normative legal research methods descriptive analysis, which is intended to provide data as possible about a situation. In this case the intended data is data that can be used as research material, which is used to determine the various statutory provisions governing the authority of the police in restoring the good name of victims of wrongful arrests.  Rehabilitation described in Article 97 paragraph (1) as follows: "a right to obtain rehabilitation if the court acquitted or freed from all lawsuits whose decision has had permanent legal force."The consequences of the law in the case of wrongful arrests should not only for the victims be wrongly alone but ought to fulfill a sense of justice in society should also have the responsibility of police investigators alone. Legal responsibilities of law enforcement in this case that should be able to apply Article 1, point 23 of the Code of Criminal Procedure mentioned rights wrongly rehabilitation.  The conclusion of this study Accountability police investigators in arresting the suspect one of them is doing the rehabilitation of suspects, where rehabilitation is continued provision of compensation. If damages are set in the two chapters, rehabilitation arranged in one article only, namely Article 97 of the Criminal Procedure Code. Thus still expected to implementing regulations. Rehabilitation is the right person to get redress in capabilities, position and dignity and dignity given to the level of investigation, prosecution, or trial since been arrested, detained, charged, or prosecuted without reason that by law or by reason of a mistake as to the person or the law is applied.  Keywords: Clear Her, Name, False Arrest